Antony & Cleopatra - "shakespeare, William" (Sweet cherry publication: China, 2012)
Antony and Cleopatra is a famous Shakespeare tragedy which follows actual events from Roman History. It is set in ancient Rome and Egypt, revolving around, Antony, a Roman General, and Cleopatra, the Queen of Egypt. Antony falls in love with Cleopatra, and throughout the play remains torn between his duty and his love for her. A simplified version of a Shakespeare classic- perfect for children aged 7+ and secondary school students looking for an easier way to access Shakespeare
Keywords: Adaptations Juvenile literature